Relationship of scrotal circumference and testicular volume to age and body weight in Dorper sheep - Ishak, Nur Ain Sakinah (2017)
This study was conducted to evaluate reproductive parameters that can be used as indicators to estimate fertility status of Dorper sheep. Scrotal circumference (SC) and testicular volume (TV) were the reproductive parameters that were measured to correlate with age and body weight. A total of 32 Dorper rams were divided into two groups: Group A (< 12 months old) and Group B (> 12 months old). There were six rams in Group A and 26 rams in Group B. The SC of the rams was measured. The length, width and height of left and right testes were measured to calculate TV. All the data were analysed statistically. The present results showed that all parameters are positively correlated to each other. The SC and TV are more correlated to body weight compared with age. The SC is positively correlated with age (r=0.605), body weight (r=0.824) and TV (r=0.925). The TV is positively correlated with age (r=0.535), body weight (r=0.873) and SC (r=0.925). This study shows that the rams of more than 12 months with body weight of at least 45kg have higher SCand TV. Therefore, age, body weight, scrotal circumference and testicular volume can be used as criteria in selection of sires.